Compassion in Practice: Perspectives of Bhutanese Primary Science Teachers - Lhamo, Jambay; Rizk, Nadya; Miller , Judith; Miller, Judith (Bhutan Journal of Research and Development, 2025)
Compassion is increasingly recognised as essential for creating safe and inclusive learning environments. In Bhutan, where compassion is deeply embedded in cultural and spiritual values, there is a growing need to strengthen teachers’ capacity to integrate compassionate practices. This study explores how primary science teachers enact compassion in their classrooms and provides practical models to inform teacher professional development. Using a sequential mixed methods approach, the study surveyed 201 primary science teachers in Bhutan and conducted in-depth interviews with ten teachers. The survey provided an overview of compassionate practices, while interviews offered deeper insights into how these practices are enacted. Six key strategies emerged: role modelling compassion, practising self-compassion, using compassionate speech, listening empathetically, understanding students’ life stories, and establishing caring classroom rules. Data show teachers create emotionally safe classrooms and foster positive relationships, with mindful compassion through presence, non-judgment, and intention central to building trust and connectedness in Bhutanese classrooms. The findings highlight that compassionate teaching is practical and can be developed through reflective practice, mindfulness, peer learning, and professional support. These insights can guide teacher training, mentorship, and reflective tools to integrate compassion and mindfulness as core pedagogical skills.